2014
DOI: 10.1111/jpy.12228
|View full text |Cite
|
Sign up to set email alerts
|

High‐throughput sequencing reveals neustonic and planktonic microbial eukaryote diversity in coastal waters

Abstract: Neustonic organisms inhabit the sea surface microlayer (SML) and have important roles in marine ecosystem functioning. Here, we use high-throughput 18S rRNA gene sequencing to characterize protist and fungal diversity in the SML at a coastal time-series station and compare with underlying plankton assemblages. Protist diversity was higher in February (pre-bloom) compared to April (spring bloom), and was lower in the neuston than in the plankton. Major protist groups, including Stramenopiles and Alveolata, domi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 27 publications
6
21
0
Order By: Relevance
“…, Egge et al. , Taylor and Cunliffe ). The studies using targeted NGS are revealing species diversity never appreciated before.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…, Egge et al. , Taylor and Cunliffe ). The studies using targeted NGS are revealing species diversity never appreciated before.…”
Section: Discussionmentioning
confidence: 98%
“…This additional culturing step hampers progress in investigating the global species diversity of Cyanidiales. Recently, targeted next-generation sequencing (NGS) has been applied to sample species diversity at an unprecedented resolution (e.g., Cuvelier et al 2010, Egge et al 2013, Taylor and Cunliffe 2014. The studies using targeted NGS are revealing species diversity never appreciated before.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies looking at general eukaryotic diversity on plastics have used a general 18S ribosomal RNA (rRNA) marker to profile communities with high‐throughput sequencing, identifying a variety of fungal taxa within their data sets (Debroas, Mone, & Ter Halle, 2017; Kettner et al., 2019; Kirstein, Wichels, Krohne, & Gerdts, 2018; Oberbeckmann et al., 2016). However, the 18S rRNA gene has limited taxonomic resolution for some fungal groups (Richards et al., 2012; Stoeck et al., 2010;Taylor & Cunliffe, 2014) and may give different profiles depending on sequenced region (De Filippis, Laiola, Blaiotta, & Ercolini, 2017). Using fungi‐specific primers, such as those targeting the Internal Transcribed Spacer regions (ITS) of the rRNA operon, ensures a high proportion of sequence reads from fungi and provide good resolution for higher fungi within Ascomycota and Basidiomycota (Andreakis et al., 2015; Rämä et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Aller et al (2005) found that the EF for bacteria and virus abundances were 10 and 7, respectively. Protistan community composition in the SML is different from the underlying waters and is enriched in some taxa (Joux et al, 2006;Cunliffe and Murrell, 2010;Taylor and Cunliffe, 2014). Joux et al (2006) proposed that buoyant particles and bubbles play a role in the enrichment of the SML with specific taxa.…”
Section: Introductionmentioning
confidence: 99%